(untitled) (Research, Society and Development, 2024)
The aim of this study was to investigate the influence of sociodemographic characteristics and health conditions on the quality of life of people living with the human immunodeficiency virus/acquired immunodeficiency syndrome. This is a cross-sectional, quantitative study with a non-probabilistic, convenience sample, carried out in a specialized care service in the state of Paraná. The WHOQOL-HIV bref instrument was used to assess quality of life. Sociodemographic data and health conditions were collected using a form. Ninety-six people took part in the study, 63 of whom were male. It was observed that the quality of life of patients aged up to 39, with a high school education or higher, showed better quality of life indicators. On the other hand, participants who considered themselves ill had a lower perception of quality of life. It was concluded that quality of life was influenced by age, schooling, self-perception of health and use of antiretroviral therapy.